Pengaruh Profitabilitas dan Likuiditas Terhadap Nilai Perusahaan Pada Perusahaan BUMN Yang Terdaftar Di BEI Periode 2016-2020 - Amelia, Dhea Ananda; Amelia, Wan Rizca (Economics, Business and Management Science Journal, 2025)
This research seeks to ascertain the impact of profitability and liquidity on company value in state-owned companies listed on the IDX for the 2016-2020 period. There are twelve state-owned businesses on the Indonesia Stock Exchange between 2017 and 2020 that were deemed to meet the assessment criteria outlined in the purposive sampling technique made up the research sample for this quantitative study, which was conducted with a population of state-owned companies listed on the Indonesia Stock Exchange between 2016 and 2020. The kind of information utilized in this research is secondary data, which originates from information seen in financial reports on the Company's official website https://www.idx.co.id/. Based on the results of the study, it was found that partially Return On Asset has a positive and substantial impact on Stock Price; partially Current Ratio has no substantial impact on Stock Price, and simultaneously Return On Asset and Current Ratio have a substantial impact on stock prices. Additionally, the coefficient of determination test findings revealed that the Adjusted R Square number was 0.304 (30.4%), which explains how the stock price can be determined and described by the current ratio and return on assets.  However, other variables or factors outside the scope of the study, such as investment policy related to dividend payout ratio, account for the remaining 69.6%.